Efficacy of transdermal flunixin in mitigating castration pain in piglets - Lopez-Soriano, Magdiel; Rocha Merenda, Victoria; Esteves Trindade, Pedro Henrique; Loureiro Luna, Stelio Pacca; Pairis-Garcia, Monique Danielle (Frontiers in Pain Research, 2022)
Castration is a painful procedure performed in swine and to date, there are no approved products available in the US to alleviate this pain. Previous work evaluating the efficacy of flunixin meglumine has shown promise in mitigating pain in swine, but no work to date has evaluated transdermal flunixin efficacy in mitigating castration pain in piglets. Therefore, the objective of this study was to evaluate the efficacy of transdermal flunixin (TDF) in mitigating castration pain utilizing a previously validated behavioral pain scale. A total of 98 Large White x Duroc cross male piglets from 98 litters were enrolled in this study. Piglets were randomly assigned to the following treatments: (1) TDF plus castration (3.33 mg/kg; CF; n = 24), (2) TDF plus sham castration (3.33 mg/kg; SF; n = 26), (3) topical physiological saline plus sham castration (S; n = 24), or (4) topical physiological saline plus castration (C; n = 24). All treatments were administered 24h prior to castration. Four-min continuous videos clips were collected 24h before castration (-24h), immediately post-castration (0h), and 24h post-castration (+24h). Video clips were then observed and scored by one trained observer using a 4-point pain scale (score 0-3) encompassing five behavioral domains of the pig acute pain scale (UPAPS). Total pain score averages were analyzed as repeated measures by analysis of variance applying a multilevel model. The UPAPS effectively distinguished varying levels of painful and non-painful states in castrated piglets as observed via deviations in total pain scores across timepoints (P<0.0001), treatment (P<0.001) and treatment*timepoint (P<0.0001). Immediately post-castration (0h), piglets in the C and CF group demonstrated greater total average pain scores than piglets in the S (P <0.03) and SF (P <0.01) groups and castrated piglets treated with TDF demonstrated lower total pain scores (P<0.05) and required less analgesic intervention immediately post-castration compared to castrated piglets receiving no treatment (P<0.0001). For C group 54% required rescue analgesia compared to 29%, 8% and 0% for CF, SF and S piglets respectively. Future work should evaluate implementation of this pain management protocol on a wide scale commercial farm setting.